Brazilian-Portuguese version of the Friendship Scale to assess social isolation: cross-cultural adaptation and psychometric properties (Research, Society and Development, 2022)
Aim: To translate, cross-cultural adapt and investigate the measurement properties of the 25-point Friendship Scale to Brazilian-Portuguese. Methods: Translation and adaptation of the 25-point Friendship Scale to Brazilian-Portuguese was conducted at first. Then, the new version was administered to 160 Brazilians to investigate test-retest reliability, internal consistency, standard error of the measurement (SEM), minimal detectable change (MDC), ceiling and floor effects, and concurrent validity. To investigate concurrent validity, the Brazilian–Portuguese version of the 0-100 EuroQol Visual Analog Scale (EQ VAS) was used to assess people’s self-reported health status. Results: The Brazilian-Portuguese version has good to excellent reliability (ICC of 0.76, 95% CI 0.61 – 0.85) and had moderate internal consistency (Cronbach’s alpha value of 0.78, 95% CI: 0.73 – 0.83). To avoid measurement error and to exceed variability, scores need to be greater than 1.33 (SEM) and 3.69 (MDC) on the 25-point scale, respectively. There was no ceiling and floor effects. For concurrent validity, there was a small positive correlation between the Friendship Scale and the EQ VAS (Spearman rs   = 0.24; p